1993
DOI: 10.1109/20.280854
|View full text |Cite
|
Sign up to set email alerts
|

Direct optical observation of vertical Bloch lines propagation by in-plane field pulses

Abstract: Abatract -Vertical Bloch line (VBL) motion in response to the in-plane fleld pulses was studied by the methods of polarized anisotropic dark fleld observation (PADO) and high-speed photography in bubble garnets. The mobility of VBLs and their velocities were measured. New types of PADO pictures which are connected with the dynamic changes of VBL and domain wall structures were observed in nonlinear region of Bloch line motion. Difference in the dynamic behavior of VBLs of different types was observed. A qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Further studies showed that the possibility of observing the Bloch lines in this dark-field configuration is related to the microscopic domain wall tilt in the VBL localization regions [21] rather than to light scattering immediately on the magnetization distribution in the Bloch line. Furthermore, another dark-field configuration making it possible to observe the Bloch lines is when the light incidence plane is parallel to the domain walls [21,76,77]. There is no illumination from either domains or domain walls in the images obtained in this configuration, while the VBLs are visualized as bright symmetric objects (Figure 7.11) regardless of magnetic topology.…”
Section: Polarized Anisotropic Dark-field Microscopymentioning
confidence: 93%
See 1 more Smart Citation
“…Further studies showed that the possibility of observing the Bloch lines in this dark-field configuration is related to the microscopic domain wall tilt in the VBL localization regions [21] rather than to light scattering immediately on the magnetization distribution in the Bloch line. Furthermore, another dark-field configuration making it possible to observe the Bloch lines is when the light incidence plane is parallel to the domain walls [21,76,77]. There is no illumination from either domains or domain walls in the images obtained in this configuration, while the VBLs are visualized as bright symmetric objects (Figure 7.11) regardless of magnetic topology.…”
Section: Polarized Anisotropic Dark-field Microscopymentioning
confidence: 93%
“…The VBLs represent stable magnetic vortices and separate domain wall regions of opposite polarity [76]. The VBL sizes in many typical ferrite-garnet films do not exceed tenths of a micrometer.…”
Section: Polarized Anisotropic Dark-field Microscopymentioning
confidence: 99%
“…The electric field of high strength was produced by a tip electrode (curvature radius R tip ~5µm) touching the surface of dielectric sample, the magnetooptical technique in Faraday geometry was used to observe the micromagnetic structure (the experimental details are described elsewhere [14]). For dynamic measurements the high speed photography technique [15] was used: the pulses of electric voltage at the tip (amplitude V=400V, pulse width ~ 300ns, the rise time ~20ns) were followed by pulses of laser ilumination (duration ~10ns) to get an image of the structure. Varying the time delay between field and laser pulses enabled us to observe the consecutive positions of domain wall and thus investigate its dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…In DWs, sections a few tens of micrometers long were observed, which moved at a noticeably lower velocity than did adjacent sections and simultaneously traveled along the DW in a direction depending on the polarity of pulses. The regularities of the motion of an isolated VBL in ferrite garnet films with perpendicular magnetic anisotropy were studied experimentally in [207][208][209] in a driving field applied in the film plane along the DW. The effect of the DW twisting on the dynamics of a VBL in a field with this orientation was studied theoretically in [210,211].…”
Section: Dynamics Of the Domain Wallmentioning
confidence: 99%